The study of dielectric diffuseness in the Ba(Mg1/3Nb 2/3)O3-BaTiO3 ceramic system - Munpakdee A. (2014)
The dielectric properties of Ba(Mg1/3Nb2/3)O 3 (BMN)-substituted BaTiO3 (BT) (xBMN-(100-x)BT) ceramics, where x ≤ 0-5mol%, were prepared by a high-temperature solid-state reaction technique. It was found that the substitution of Mg2+ and Nb 5+ at the Ti-site of the BMN-BT ceramics caused compositional inhomogeneity, leading to a diffuse phase transition (DPT). Discontinuous grain growth accompanied with excellent dielectric diffuseness was found in 3-5mol% BMN specimens. The maximum solubility limit of Mg/Nb substitution was assumed to be between 3<x<4mol% BMN. A dielectric study of these compounds as a function of temperature suggested that, for the ceramics with x>2mol%, the maximum dielectric constant decreased and the Curie temperature shifted downwards on the lower temperature side. © 2006 IOP Publishing Ltd.